Partisipasi Masyarakat Dalam Implementasi Kebijakan Roti 7 Lapis Dinas Pemadam Kebakaran Dan Penyelamatan Kota Surabaya - Najwa Tsaniya Anjainah; Ajeng Dwi Larasati; Dewi Rahma Aprilia Paramita; Binti Azizatun Nafi’ah (Public Service and Governance Journal, 2025)
This study aims to analyze the level of community participation in the “Roti 7 Lapis” program (Response Time 7 Minutes of Free Fire Service) initiated by the Surabaya Fire and Rescue Department. Using a descriptive qualitative approach and Arnstein’s ladder of participation theory, the research explores citizen involvement in reporting, prevention, and early fire response. Data were collected through interviews and observations in two densely populated areas: Sidotopo Jaya and Kedung Rukem. The findings indicate that community participation has reached the "citizen control" level within the partnership stage, although it is not evenly distributed across regions. The main challenges include low public awareness, hoax reports to the 112 call center, and limited access for fire trucks due to environmental conditions. This study demonstrates that the success of the program relies not only on rapid response but also on efforts to foster meaningful community engagement. These findings contribute to the literature on participatory public policy within the context of urban emergency services.